Approach to the social conflict, from the road blockade and the aimara culture: Puno department case. - Rayter Arnao, David Guillermo Martín (2023)
On December 7, 2022, former President Pedro Castillo announces the temporary closure of Congress, without the support of the armed forces, institutions, or citizens, resulting in a presidential vacancy due to “permanent moral incapacity” and his arrest. Part of the population considers that the vacancy and the arrest of the former president were not carried out following due process, which exacerbates the mood, producing demonstrations that translate into road blockades, burning of institutional premises among other disturbances; with a balance of more than 60 deaths. This article aims to make an approach to understand why there are greater conflicts in the Puno region than in the rest of the country and to what extent these social conflicts and road blockages are related to the fact of the presence of the Aymara culture, historical factors, HDI or even to external or external factors. sector interests. For this purpose, the qualitative approach of documentary design and official data was used for the analysis; determining the relationship between the factors indicated with the highest concentration of protests. This approach is part of the ongoing research regarding social conflicts in Puno. [1] Aimara People (Aymara), an indigenous people that covers the high plateau area of the departments of Puno, Moquegua and Tacna in Peru, as well as a presence in Argentina, Bolivia and Chile. [2]   Human development index, an indicator that measures progress, used since 1990 by the United Nations Development Program (UNDP).